2019
DOI: 10.1016/j.heliyon.2019.e02199
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of suprapatellar versus infrapatellar intramedullary nailing for the treatment of tibial shaft fractures

Abstract: BackgroundWhether the optimal treatment for tibial shaft fractures is suprapatellar intramedullary nailing or infrapatellar approach is controversial.Materials and methodsPubMed, Embase, Cochrane, Web of science and CNKI, Wan fang Chinese databases were retrieved from their establishment to April 26, 2017. Seven studies (three randomized and four clinical controlled trials) were included in the final analysis. This meta-analysis included 683 patients with tibial shaft fracture (suprapatellar: 341; infrapatella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…20 A further metaanalysis by Xu et al supports our finding of lower incidence of anterior knee pain following SPN tibial nailing. 21 However, it is important to bear in mind that this new approach is not free from complications. A recent study evaluated 139 open tibial shaft fractures which were managed by an SPN approach 22 and demonstrated, in a single case, that septic arthritis of the knee joint may occur following SPN tibial nailing.…”
Section: Discussionmentioning
confidence: 99%
“…20 A further metaanalysis by Xu et al supports our finding of lower incidence of anterior knee pain following SPN tibial nailing. 21 However, it is important to bear in mind that this new approach is not free from complications. A recent study evaluated 139 open tibial shaft fractures which were managed by an SPN approach 22 and demonstrated, in a single case, that septic arthritis of the knee joint may occur following SPN tibial nailing.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple studies and meta-analyses in the literature comparing the extent of knee pain between supra and infrapatellar approaches [ 5 , 6 , 24 , 25 ]. The common point of most of these studies was that they all concluded that there was no difference between the two approaches regarding anterior knee pain by evaluation of scores over longer periods (12 months and above).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [7] discovered a decrease in fluoroscopy time with a mean of 80.61 ± 37.23 s in the SP group compared to 118.68 ± 40.23 s in the IP group ( P = .009). Recent meta-analyses comparing the SP and IP approaches confirm significant reduction in fluoroscopy time with the SP approach [3,7,8,10,20] . MacDonald et al, [6] in a multicenter clinical trial, noted there to be no significant difference between operating or fluoroscopic time between the 2 groups.…”
Section: Intraoperative Fluoroscopymentioning
confidence: 99%
“…Two recent meta-analyses show a decreased operative time with the SP approach. [3,10] Xu et al, [10] comparing 7 studies (3 randomized; 4 clinical controlled trials), found the IP approach to be more time consuming than the SP approach (P = .01). Chen et al [3] evaluated 7 randomized controlled trials (RCT) and originally found no significant difference in operative time (P = .88); however, sensitivity analysis excluding an outlier study did show a significant reduction in operative time with the SP approach (P = .002).…”
Section: Operative Timementioning
confidence: 99%